Clinical phenotyping of spondylodiscitis and isolated spinal epidural empyema: a 20-year experience and cohort study - Hijazi, Mido Max; Siepmann, Timo; El-Battrawy, Ibrahim; Glatte, Patrick; Eyüpoglu, Ilker; Schackert, Gabriele; Juratli, Tareq A.; Podlesek, Dino (Frontiers in Surgery, 2023)
Background The incidence of spondylodiscitis (SD) and isolated spinal epidural empyema (ISEE) has been increasing in the last decades, but the distinct differences between both entities are poorly understood. We aimed to evaluate the clinical phenotypes and long-term outcomes of SD and ISEE in depth. Methods We performed a chart review and analyzed data from our cohorts of consecutive SD and ISEE patients who were treated and assessed in detail for demographic, clinical, imaging, laboratory, and microbiologic characteristics at a university neurosurgical center in Germany from 2002 to 2021. Between-group comparisons were performed to identify meaningful differences in both entities. Results We included 208 patients (72 females: age 75 [75 32–90] y vs. 136 males: 65 [23–87] y, median [interquartile range], p < 0.001), of which 142 (68.3%) had SD and 66 (31.7%) had ISEE. Patients with SD were older than ISEE (ISEE: 62 y vs. SD: 70 y, p = 0.001). While SD was more common in males than females (males: n = 101, 71.1% vs. females: n = 41, 28.9%, p < 0.001), there was no sex-related difference in ISEE (males: n = 35, 53.0% vs. females: n = 31, 47.0%, p = 0.71). Obesity was more frequent in ISEE than in SD (ISEE: n = 29, 43.9% vs. SD: n = 37, 26.1%, p = 0.016). However, there were no between-group differences in rates of diabetes and immunodeficiency. In the entire study population, a causative pathogen was identified in 192 (92.3%) patients, with methicillin-susceptible staphylococcus aureus being most frequent (n = 100, 52.1%) and being more frequent in ISEE than SD (ISEE: n = 43, 65.2% vs. SD: n = 57, 40.1%, p = 0.003). SD and ISEE occurred most frequently in the lumbar spine, with no between-group differences (ISEE: n = 25, 37.9% vs. SD: n = 65, 45.8%, p = 0.297). Primary infectious sources were identified in 145 patients (69.7%) and among this skin infection was most common in both entities (ISEE: n = 14, 31.8% vs. SD: n = 25, 24.8%, p = 0.418). Furthermore, epidural administration was more frequent the primary cause of infection in ISEE than SD (ISEE: n = 12, 27.3% vs. SD: n = 5, 4.9%, p < 0.001). The most common surgical procedure in SD was instrumentation (n = 87, 61%) and in ISEE abscess evacuation (n = 63, 95%). Patients with ISEE displayed lower in-hospital complication rates compared to SD for sepsis (ISEE: n = 12, 18.2% vs. SD: n = 94, 66.2%, p < 0.001), septic embolism (ISEE: n = 4/48 cases, 8.3% vs. SD: n = 52/117 cases, 44.4%, p < 0.001), endocarditis (ISEE: n = 1/52 cases, 1.9% vs. SD: n = 23/125 cases, 18.4%, p = 0.003), relapse rate (ISEE: n = 4/46, 8.7% vs. SD: n = 27/92, 29.3%, p = 0.004), and disease-related mortality (ISEE: n = 1, 1.5% vs. SD: n = 11, 7.7%, p = 0.108). Patients with SD showed prolonged length of hospital stay (ISEE: 22 [15, 30] d vs. SD: 38 [29, 53] d, p < 0.001) and extended intensive care unit stay (ISEE: 0 [0, 4] d vs. SD: 3 [0, 12] d, p < 0.002). Conclusions Our 20-year experience and cohort analysis on the clinical management of SD and ISEE unveiled distinct clinical phenotypes and outcomes in both entities, with ISEE displaying a more favorable disease course with respect to complications and relapse rates as well as disease-related mortality.